The Problem Of Elimination Of Illiteracy By Writing Textbooks In The Steppe - Almas Naimanbaev, Kenan Koch, Yerkinbek Turgunov, Yedilbek Abdimomynov Baktiyar Smanov, Rozalinda Shakhanova, (Opción, 2019)
This article is devoted to the methodical work of Beyimbet Maylin and Mukhtar Auezov, insufficiently known to the general public as one of the aspects of their versatile activity. As a result, the first group of developers of the programs in Kazakhstan not only showed what to teach, but also considered the question - how to teach. In conclusion, we would like to say that one of the aspects of writers-dramatists of Beyimbet Maylin and Mukhtar Auezov -which is not opened yet is not investigated in a due measure- is their work as teachers-methodologists.